Counterion‐Paired Bright Heptamethine Fluorophores with NIR‐II Excitation and Emission Enable Multiplexed Biomedical Imaging. (12th April 2022) - Yang, Yang; Sun, Caixia; Wang, Shangfeng; Yan, Kui; Zhao, Mengyao; Wu, Bin; Zhang, Fan
Abstract: Photon excitation and emission at the NIR‐II spectral window enable high‐contrast deep‐tissue bioimaging. However, multiplexed imaging with NIR‐II excitation and emission has been hampered by the limited chemical strategies to develop bright fluorophores with tunable absorption in this spectral regime. Herein, we developed a series of heptamethine cyanines (HCs) with varied absorption/emission maxima spanning from 1100 to 1600 nm through a physical organic approach. A bulky counterion paired to HCs was found to elicit substantial improvements in absorptivity (7‐fold), brightness (14‐fold), and spectral profiles in water, addressing a notorious quenching problem of NIR‐II cyanines due to aggregation and polarization. We demonstrated the utilities of HC1222 and HC1342 for high‐contrast dual‐color imaging of circulatory system, lymphatic structures, tumor, and organ function in living mice under 1120 nm and 1319 nm excitation, showing HCs as a promising platform for non‐invasive bioimaging. Abstract : A series of heptamethine cyanines (HCs) has absorption/emission maxima spanning from 1100 to 1600 nm. A counterion‐paired strategy was explored to improve the brightness of HCs in aqueous solution by reducing aggregation and polarization. Profiting from enhanced brightness and well‐shaped absorption spectra, dual‐color imaging based on NIR‐II excitation and emission was performed in living mice for the first time.